Isolation and Characterization of Enterococcus faecalis-Infecting Bacteriophages From Different Cheese Types - Beatriz del Rio; Beatriz del Rio; Esther Sánchez-Llana; Noelia Martínez; María Fernández; María Fernández; Victor Ladero; Victor Ladero; Miguel A. Alvarez; Miguel A. Alvarez (Frontiers in Microbiology, 2021)
Enterococci are a diverse group of Gram-positive, lactic acid bacteria (LAB). They are found in many environments, including fermented foods, in which they could constitute a health threat since they produce biogenic amines, which consumption can lead to intoxication. Moreover, enterococci has also emerged as an important hospital-acquired pathogens via its acquisition of antimicrobial resistance. Bacteriophages possess features that make them optimal biotechnological weapons for controlling bacterial growth in disease and food spoilage contexts. However, no silver bullet bacteriophage exists that can eliminate all the undesirable bacteria in a complex environment. Rather, a combination of phages with different host ranges would be required which implies the need for large collections of diverse phages. This work reports the isolation of several Enterococcus faecalis-infecting bacteriophages from different types of cheese, along with the range of E. faecalis strains of diverse origin (from dairy to clinical environments) they are able to infect. The isolated phages showed a large diversity regarding the number and origin of strains they infect. Some of these phages were subjected to morphological and genomic characterization which confirmed their diversity and showed they belong to different families and genera. The present findings increase the potential arsenal for the bacteriophage-based biocontrol of harmful E. faecalis populations.